Suspended liminality: breastfeeding and becoming a mother in two NICUs - Shattnawi, Khulood Kayed (International Journal of Advanced Nursing Studies, 2015)
Objectives: This paper presents the results of an ethnographic study of breastfeeding and mothers’ experiences within two neonatal intensive care units (NICU).Methods: The data collection involved 135 hours of participant observation over a 6-month period and semi-structured interviews of 17 mothers.Results: Data analysis showed that the mothers faced many obstacles that prohibited them from practicing breastfeeding within the NICUs, which impacted on their experiences as mothers. Their experiences were revealed as a developing process as their feeling changed from fearful and terrifying toward becoming and feeling like a ‘real’ mother. Four distinct themes emerged; the first highlighted the crisis, which involved the mother's feelings of emotional instability, their strategies for coping such as not visiting the baby, and recognition of the NICU as a stressful environment. The second theme described issues relating to control and power. This involved the perception of having a lack of control and needing to seek permission, the use of language as a mechanism for control, and mothers being placed in a subordinate role. The third theme related to the separation, which included difficulties of acceptance, feeling like stranger and not being important, and the need for physical closeness. The final theme, becoming a mother, included issues such as the special moments, breastfeeding as a turning point, and practical and informational needs.Conclusions: A finding suggests that mothers, who deliver prematurely, may have their rite of passage into motherhood interrupted, resulting in them being placed in a position of suspended liminality.